UTILIZAÇÃO DE RESÍDUOS POLIMÉRICOS DA INDÚSTRIA DE RECICLAGEM DE PLÁSTICO EM BLOCOS DE CONCRETO - Viana, Ednilson; Mattar, Danilo Charbel (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2013)
http://dx.doi.org/10.5902/223611706471 The fate of polymeric wastes for purposes other than those landfills, such as use in concreteblocks, is characterized as an important measure of recovery of solid waste and reducing waste ofraw materials. Thus, this study was aimed to analyze the technical feasibility of using wastepolymeric stranded segment of plastic industries in the production of concrete blocks. To achievethis goal, the material was ground in generating company in the plastics and sent to study theproduction of concrete blocks in company specializing in the business. Soon after, the block wentfor tests of Compressive Strength, Verification surface, dimensional analysis, Water absorption andleaching. Performed tests, it was observed that only approved the bricks with 5% plastic, which didnot present any problem structure and therefore concluded ideal as the percentage ofincorporation of such material into concrete blocks.